PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ELEKTRONIK VIDEO ANIMASI TERHADAP EFEKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK DI SMP SWASTA YPK PEMATANG SIANTAR - Nadira Tanjung, Fathyah; Dianti Siboro, Thiur; Damanik, Risjunardi (Jurnal Metabio, 2023)
This study aims to determine the effect of the use of animated video electronic learning media on the effectiveness and learning outcomes of students at YPK Pematang Siantar Private Junior High School. The population in this study was all grade VIII consisting of 4 classes with a total of 98 students. Sampling was carried out using a purposive sampling technique, namely with 2 classes with a total of 48 students. The results of the data analysis showed that the average score of the experimental class questionnaire was 58.12 and the average for the control class was 74.99. The pretest of the experimental class was 39.16 while the pretest of the control class was 41.04. And after being given treatment using animated video electronic media, the average posttest score of the experimental class was 81.66 while the average posttest score of the control class was 77.5. Based on the results of the test questions, a sig. (2-tailed) value was obtained. Test results. Based on the table above, the Sig. value. (2-tailed) of 0.034 < 0.05 with tcount (2.256)>ttable (1.714) on df 23, then Ha is accepted. Therefore, the conclusion is that animated video electronic learning media has an effect on the effectiveness and learning outcomes of students at SMP YPK Pematang Siantar. And the results of the effectiveness questionnaire based on the table above, the Sig. value (2-tailed) of 0.000 < 0.05 with tcount (8.660)>ttable (1.714), then Ha is accepted. Therefore, the conclusion is that animated video electronic learning media has an effect on the effectiveness and learning outcomes of students at SMP YPK Pematang Siantar.